1975
DOI: 10.1073/pnas.72.4.1309
|View full text |Cite
|
Sign up to set email alerts
|

Amino-acid sequence of parvalbumin from rabbit skeletal muscle.

Abstract: Determination of the complete aminoacid sequence of rabbit skeletal muscle parvalbumin is described. The sequence of 86 of the 109 total residues was determined automatically by sequenator analyses of peptides obtained after cleavage with CNBr or with trypsin. The positions of the remaining 23 residues were determined by subtractive Edman degradation of tryptic and chymotryptic peptides. The protein has an acetylated amino terminus. Comparison of the rabbit parvalbumin with those from carp, hake, and pike and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…'Mac Manus & Whitfield (1983). 'Enfield et al (1975). figure 3: Typical plots of In y versus r2 plot for SMCaBP-11.…”
Section: Resultsmentioning
confidence: 99%
“…'Mac Manus & Whitfield (1983). 'Enfield et al (1975). figure 3: Typical plots of In y versus r2 plot for SMCaBP-11.…”
Section: Resultsmentioning
confidence: 99%
“…1 b). Out of 110 amino acid residues, 8 are exchanged between mouse and rat, 18 between mouse and rabbit (Enfield et al 1975) and 16 between rat and rabbit. Five residues are identical in rat and rabbit, but differ in mouse PV.…”
Section: (I) Isolation and Sequencing Of A Mouse Parvalbumin Cdna Clonementioning
confidence: 99%
“…Positions whose amino acid is identical in all 20 sequences are enclosed in boxes. The taxa are: pike = Esox lucinus (Frankenne et al 1973;Gerday 1976); coelacanth = Latimeria chalumnae (Jauregui-Adell and Pechire 1978; Pechere et al 1978); amphiuma = Amphiuma means; frog = Rana esculentu (Capony et al 1975;Jauregui-Adell et al 1982); rabbit = Oryctolugus cuniculus (Enfield et al 1975); thomback ray = Ruju cluveutu (Thatcher and Pechere 1977); turtle = Gruptemys geogruphicu; boa = Boa constrictor; whiting = Gudus merlungus (Joassin and Gerday 1977); cod = Gudus cullarias (Elsayed and Bennich 1975); hake = Merluccius merluccius ); chub = Leuciscus cephulus (Gerday et al 1978); electric eel = Electrophorus electricus (Zhu et al 1984 bridge, and Leu-79, which is responsible for hydrogen binding with . The function of Phe-72 and Thr-84 is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The recent studies on the parvalbumins in muscles of rabbit (Lehky et al 1974;Enfield et al 1975), rat (Berchtold et al 1982), and chicken (Heizmann and Strehler 1979), however, have revealed the presence of this protein in a wider range of vertebrates. Because of their relative ease of purification and small size, interest in this family of homologous proteins in systematic study has increased (Pechire et al 1973;Goodman and Pechere 1977;Goodman et al 1979).…”
Section: Introductionmentioning
confidence: 99%